Novel Inhibitor of Keap1-Nrf2 Protein-Protein Interaction Attenuates Osteoclastogenesis In Vitro and Prevents OVX-Induced Bone Loss In Vivo - Zhihao Chen; Hongyuan Yao; Alessandra Marie Encarnacion; Jujin Jeong; Yunju Choi; Sangwook Park; Sunwoo Lee; Taehoon Lee (MDPI AG, 2024)
Keap1 interacts with Nrf2 by assisting in its ubiquitination and subsequent proteolysis. By preventing ROS accumulation during RANKL-induced osteoclastogenesis, Nrf2 activation can prevent the differentiation of osteoclasts. Additionally, inhibiting the Keap1-Nrf2 PPI can be an effective strategy for triggering Nrf2 to regulate oxidative stress. Structure-based virtual screening was performed to discover a potentially novel Keap1-Nrf2 PPI inhibitor wherein KCB-F06 was identified. The inhibitory effects of KCB-F06 on osteoclastogenesis were investigated in vitro through TRAP staining and bone resorption assays. An ovariectomy-induced osteoporosis mouse model was applied to evaluate KCB-F06's therapeutic effects in vivo. Lastly, the underlying mechanisms were explored using real-time PCR, Western blotting, and co-IP assays. KCB-F06 was discovered as a novel Keap1-Nrf2 PPI inhibitor. As a result, the expression of antioxidants (HO-1 and NQO1) was suppressed, hence reducing ROS accumulation during osteoclastogenesis. Subsequently, this caused the inactivation of RANKL-induced IKB/NF-kB signaling. This eventually led to the downregulation of osteoclast-specific proteins including NFATc1, which is an essential transcription factor for osteoclastogenesis. These results demonstrated that Nrf2 activation in osteoclasts is a valuable tool for osteoclastic bone loss management. In addition, KCB-F06 presents as an alternative candidate for treating osteoclast-related bone diseases and as a novel small molecule that can serve as a model for further Keap1-NRF2 PPI inhibitor development.